Community Interpretation Study of Parks and Destries in Medan City - Novalinda, Novalinda (Budapest International Research and Critics University, 2021)
Indonesia is a country with various ethnic cultures and religions. And the city of Medan is one area that has a diversity of ethnicities and religions, with this difference sometimes it will cause a difference and the principle of how to understand the interpretation of an object problem park is open land that is used to get pleasure, joy, and comfort both in housing (houses/ residential complexes) and in the city. And the park is equipped with facilities that support the community and the environment. And the link between the park and its environment is the pedestrian. Pedestrian is a word that is absorbed in a foreign language which means pedestrians, which is closely related to open spaces in a city, This study examines the local wisdom found in the community in utilizing the use of parks and destrins which are a form of human behavior and the natural environment and seeks to be able to provide concepts and strategies that can be used by the community to help increase awareness to participate actively in improving the quality of the environment. surrounding. Community Interpretation of Parks and Destroying is a method or way of how people view using parks and pedestrian paths as facilities to enjoy the feel of a park, this is because pedestrians are the main indicator for the progress of civilization and future city development. For this reason, it is necessary to anticipate it by carrying out several approaches to the community.